The Effect of Administration of Lavender and Lemon Aromatherapy on Emesis Gravidarum - Dinengsih, Sri; Utami, Dinda Ferizka (Jurnal MIDPRO, 2023)
The incidence of hyperemesis gravidarum in Indonesia in 2015 was 1.5-3% of pregnant women Prolonged and poorly treated nausea and vomiting can affect nutritional disorders, dehydration, weakness, weight loss, and electrolyte imbalances, if not treated immediately this nausea and vomiting can interfere with daily life, or better known as hyperemesis gravidarum. This study is to determine the effect of giving lavender and lemon aromatherapy on emesis gravidarum in TPMB R in 2022. This study used a type of quasi experiment with a two group pretest-postest design. The population in this study were first and second trimester pregnant women at TPMB R with a total sample of 53 respondents. The sample of this study amounted to 30 people with purposive sampling technique, namely sampling based on exclusion and inclusion criteria. Bivariate analysis using the Paired T test. The average value of the level of emesis gravidarum before being given lavender aromatherapy (10.07) and the average level of emesis gravidarum after being given lavender aromatherapy (5.67) with a difference in the level of Emesis Gravidarum (4.40). The average level of Emesis Gravidarum before being given lemon aromatherapy (11.47) and the average level of emesis gravidarum after being given lemon aromatherapy (6.27) with a difference in emesis gravidarum (5.20). There is an effect of giving Levender Aromatherapy on Emesis Gravidarum (p-Value 0.001) and there is an effect of giving lemon aromatherapy on Emesis Gravidarum (p-Value 0.000). There is no difference between giving lavender aromatherapy and lemon aromatherapy on Emesis Gravidarum because both have the same effectiveness. It is hoped that lavender aromatherapy and lemon aromatherapy can be used as alternative treatments to reduce nausea and vomiting in pregnant women that can be done at home.